Henry Adams in the Secession Crisis : Dispatches to the Boston Daily Advertiser, December 1860-March 1861 - Adams, Henry, 1838-1918 (Book collections on Project MUSE., 2012)
During the Secession Winter session of Congress, twenty-two-year-old Henry Adams worked as private secretary to his father, Representative Charles Francis Adams. Henry wrote four accounts of these crucial months in Washington-an essay, letters to his brother, a segment in his famous autobiography, and twenty-one unsigned letters that Adams composed as a novice correspondent for the Boston Daily Advertiser. Henry Adams in the Secession Crisis presents the Advertiser letters for the first time since their original publication between 1860 and 1861.